Growth Performance of African Catfish Clarias gariepinus (Burchell, 1822) Fed with Varying Inclusion Levels of Watermelon (Citrullus lanatus) Bark - Patrick Ozovehe Samuel; Paul Ozovehe Sadiq; Adesola V. Ayanwale; Adamu Z. Mohammed; Victoria Victoria; I. Chukwuemeka (Journal of Aquaculture and Fish Health, 2022)
The cost incurred in raising fish to table size in fish farming has been a major issue both to the farmers and the consumers at large. To address this concern this study assessed the growth performance of Clarias gariepinus fed varying inclusion levels of water melon (Citrullus lanatus) bark. A total of 120 samples with 0.75±0.209g mean weight and 3.9±0.31cm mean total length were acclimated in the laboratory for a period of 14 days during which they were fed to satiation twice daily. Subsequently, they were randomly assigned to the five treatments diets with replicate in each case at 12 fish per treatment; T1 with 00%, T2 with 25%,  T3 with 50%, T4 with 75% and T5 with 100% levels of inclusion as possible replacement for equal weight of soybeans. The set-up ran for 12 weeks and the growth parameters (lengths and weight) were determined on weekly basis. Weight gain and specific growth rate were calculated. The physico-chemical parameters of the test media were also determined on weekly basis according to standard methods. The data generated were subjected to one way analysis of variance. From the results: Treatments with 50% and 75% inclusion levels performed slightly better than the control in terms of weight gain. The highest weight obtained in T2 and T3 were 31.71±0.35g and 31.48±1.71g, respectively. Similarly, the optimum requirement of watermelon bark level in the formulation of practical diets for improved growth of C. garienpinus were 50% and 75% in terms of lengths. T2 and T3 had the highest total lengths with 19.05±0.35cmand 15.90±2.80cm, respectively; while the standard lengths in T2 and T3 were 13.50±0.35cmand 13.45±2.85, respectively. Hence, water melon bark can replace the more expensive soybean thereby reducing cost of production and curtail environmental filth and disposal problems associated with watermelon bark waste in Nigeria.